2018
DOI: 10.1111/jph.12682
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of microbial diversity and bacterial seedling disease‐suppressive activity in organic‐farmed and standardized commercial conventional soils for rice nursery cultivation

Abstract: The outbreak of rice plant diseases can be effectively suppressed in organic farming systems. However, the mechanisms of disease suppression by organic farming systems are not well understood. When Burkholderia‐infected rice seeds were sown and cultivated on nine organic‐farmed soils which were supplied by nine independent organic rice farmers or standardized commercial conventional soils, the emergence of bacterial seedling diseases was suppressed to equivalent degrees in nine organic‐farmed soils, whereas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 73 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…Organic farming is becoming popular worldwide and has, in some cases, been proposed to contribute to the higher disease resistance of crops than conventional farming. Based on the findings of a microbiomic analysis, Takahashi et al (30) demonstrated that the physicochemical properties of soils were not directly associated with the disease suppressive properties of rice seedlings against pathogenic Burkholderia spp. ; however, bacterial populations showed greater diversities in organic soils than in conventional soils.…”
mentioning
confidence: 99%
“…Organic farming is becoming popular worldwide and has, in some cases, been proposed to contribute to the higher disease resistance of crops than conventional farming. Based on the findings of a microbiomic analysis, Takahashi et al (30) demonstrated that the physicochemical properties of soils were not directly associated with the disease suppressive properties of rice seedlings against pathogenic Burkholderia spp. ; however, bacterial populations showed greater diversities in organic soils than in conventional soils.…”
mentioning
confidence: 99%
“…Though the effect was likely due to a combination of multiple factors, the phage seemed to contribute to disease suppression by lysing multiple strains of B. glumae and B. plantarii in rice seeds in the soil for their cultivation. Otherwise, while organically farmed soils with a disease suppression effect have been shown to harbor more diverse and more robust bacterial structures than conventional commercial soils [ 37 ], polyvalent phages might contribute to maintaining a robust bacterial population, which can lead to the suppression of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Co. Ltd., Iwate, Japan) that had been sterilized by autoclaving (HVE-50, Hirayama Manufacturing Corporation, Saitama, Japan) at 140 °C for 10 min and kept at 30 °C for 8 days under a 14-h light (14,000 lux)/10-h dark cycle in a growth chamber (KG-201 HL-D, Koito, Yokohama, Japan). The severity of symptoms for each individual seedling was evaluated according to a previously described method [ 36 , 37 ]. Briefly, for each plant, the disease severity score was evaluated on a scale of 0–3 (0: healthy; 3: completely dead) and the disease severity index was calculated as follows: ((1 A + 2 B + 3 C )/3 N ) × 100, where N is the total number of plants and A , B , and C, respectively, represent the number of plants rated 1, 2, or 3 on the above scale.…”
Section: Methodsmentioning
confidence: 99%
“… Zhao et al (2016) noticed that applying pig manure organic–inorganic compound fertilizer while reducing the use of chemical fertilizer could enrich microorganisms related to the carbon-nitrogen cycle, promote nitrification and conversion of organic matter, raise enzyme activity and the amount of microorganisms, and boost plant growth and grain yield. A comparative test conducted by Takahashi et al (2018) showed that compared with conventional cultivation, organic farming was more capable of diversifying and stabilizing the bacterial population in soil, which greatly suppressed rice diseases. All the above-mentioned results testify the advantage of organic farming.…”
Section: Introductionmentioning
confidence: 99%